Sons da quebrada e da calçada como territórios da música em Aracaju. Ou sobre como a cidade diz onde cada música deve circular - Conceição, Aline Braga Farias (2021)
The supposed dichotomy registered in the names Som de Calçada and Som de Quebrada, objects of the analysis proposed here, gives rise to reflections and tensions about the relationship between music and public space in the capital of Sergipe, Aracaju. In spite of what the denominations of the movements can give rise to, namely: an alleged rivalry between the collectives that carry out these appropriations, the terms “calçada” and “quebrada” denounce a logic of building cities and disputing forms of life. Our hypothesis is that, as musical movements established in territorialities in the urban public space, these phenomena could demonstrate how the capitalist logic of production is present in the two dimensions raised by the Som de Quebrada and Som de Calçada, the cultural industry and the urbanization. In both dimensions, pavement and quebrada, as categories, are symbols of a hierarchy of differences used in the segregation of music and the city. Our research path to investigate this hypothesis begins with field observations. Interviews, a survey and production of concept maps were also carried out by Som de Quebrada and Calçada participants. The gaze directed at the phenomena will be guided by the dialectical method of historical materialism, based on the understanding that the phenomena must be analyzed in their dimension of historicity, totality and contradictions. In this text, we bring in chapter 1 the discussion about music, linked to the cultural industry, based on studies of the Political Economy of Communication and Culture, from a Latin American perspective. In chapter 2, dedicated to sounds and urban space, we bring the discussion about territorialities and data about the urbanization of the city of Aracaju. In chapter 3, aimed at analyzing the research corpus as from the discussions carried out in the previous chapters, we present how the sounds of calçada and quebrada are inserted in the city space and we bring the conceptual maps produced by the participants, who record their musical trajectories in the city, having as reference these appropriations of public space, and that reveal, in a segregating way, how the city of Aracaju says where each music should circulate.